Emotional intelligence and compulsive buying in students of the Federico Villarreal National University, Lima 2020 - Espinoza Urbina, Carlos Alfredo (2022)
The purpose of this article was to determine the relationship between emotional intelligence and compulsive shopping. The Meta-humor trait scale (TMMS-24), adapted by Fernández Berrocal, Extremera and Ramos, and the Compulsion Purchase survey by Valence, Fortier and Astous, were administered to 97 undergraduate Psychological Sciences students from a national college in Lima (32 men and 65 women), between 19 and 34 years old. A negative and significant correlation was obtained between both variables (r = -.301, p <.1). No statistically significant differences were found according to gender for emotional intelligence; however, differences were found in terms of compulsive shopping, with a slight tendency towards women, with a frequency of 29, compared to men of 8. The descriptive results for the indices regarding emotional intelligence showed a higher incidence in the category of "adequate" with a percentage of 74.2%, "excellent" 13.4% and "needs improvement" 12.4% respectively; for the levels of compulsive buying, there is a higher percentage for the category of "Non-compulsive" with 61.9% and "compulsive" with 38.1%. It is concluded that the higher the emotion perception indices, the lower the level of compulsive buying. Keywords: Emotional intelligence; compulsive shopping; students.